1999
DOI: 10.1364/ao.38.002824
|View full text |Cite
|
Sign up to set email alerts
|

Profile measurement taken with liquid-crystal gratings

Abstract: Profile measurement taken with liquid-crystal gratings and a phase-shifting technique is proposed, and its effectiveness is verified by experiment. The surface profile is obtained by measurement of the phase distributions of the sinusoidal gratings deformed by an object's surface. The liquid-crystal grating gives an accurate phase shift, an arbitrary projection pitch, and a constant surface brightness compared with conventional gratings such as a laser interference fringe grating and a Ronchi grating. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…Because the commercial DLP projector is typically a nonlinear device, the nonlinearity could introduce periodic phase error in the conventional fringe patterns if it is not handled properly. Numerous approaches have been proposed to either actively [15,16] or passively [17][18][19][20] correct the errors caused by nonlinear gamma. In this research, we used a technique introduced in [16] to actively deform the projected fringe patterns.…”
Section: B Phase Error Determinationmentioning
confidence: 99%
“…Because the commercial DLP projector is typically a nonlinear device, the nonlinearity could introduce periodic phase error in the conventional fringe patterns if it is not handled properly. Numerous approaches have been proposed to either actively [15,16] or passively [17][18][19][20] correct the errors caused by nonlinear gamma. In this research, we used a technique introduced in [16] to actively deform the projected fringe patterns.…”
Section: B Phase Error Determinationmentioning
confidence: 99%
“…Unlike a structured light system using a binary coding method, the DFP system requires calibrating for the nonlinearity of the projection and compensating for the errors associated with it. Even though nonlinearity correction is relatively mature with many methods developed, [19][20][21][22][23][24] our research found that the nonlinearity of the projector actually changes over time; this complicates the problem since a regular nonlinearity calibration is usually sufficient. 5 Nevertheless, good quality phase can be obtained after applying a proper nonlinear gamma correction algorithm.…”
Section: Projector Nonlinear Gamma Correctionmentioning
confidence: 91%
“…Overall, these methods can be classified into two categories: actively modifying the fringe patterns before their projection, 10 or passively compensating the phase error after the fringe patterns are captured. [11][12][13][14][15][16][17][18][19][20][21][22][23] The majority research focused on estimating the gamma coefficients of the projector through different algorithms from the captured fringe patterns, and some by directly calibrating the gamma of the projector. Both active and passive methods have been proved successful in substantially reducing the nonlinearity error caused by the projector.…”
Section: Introductionmentioning
confidence: 99%